Addition of Fructooligosaccharides and Dried Plum to Soy-Based Diets Reverses Bone Loss in the Ovariectomized Rat - Johnson, Catherine D. (Hindawi Publishing Corporation, 2011)
Dietary bioactive components that play a role in improving skeletal health have received considerable attention in complementary and alternative medicine practices as a result of their increased efficacy to combat chronic diseases. The objectives of this study were to evaluate the additive or synergistic effects of dried plum and fructooligosaccharides (FOS) and to determine whether dried plum and FOS or their combination in a soy protein-based diet can restore bone mass in ovarian hormone deficient rats. For this purpose, 72 3-month-old female Sprague-Dawley rats were divided into six groups (n = 12) and either ovariectomized (Ovx, five groups) or sham-operated (sham, one group). The rats were maintained on a semipurified standard diet for 45 days after surgery to establish bone loss. Thereafter, the rats were placed on one of the following dietary treatments for 60 days: casein-based diet (Sham and Ovx), soy-based diet (Ovx + soy) or soy-based diet with dried plum (Ovx + soy + plum), FOS (Ovx + soy + FOS) and combination of dried plum and FOS (Ovx + soy + plum + FOS). Soy protein in combination with the test compounds significantly improved whole-body bone mineral density (BMD). All test compounds in combination with soy protein significantly increased femoral BMD but the combination of soy protein, dried plum and FOS had the most pronounced effect in increasing lumbar BMD. Similarly, all of the test compounds increased ultimate load, indicating improved biomechanical properties. The positive effects of these test compounds on bone may be due to their ability to modulate bone resorption and formation, as shown by suppressed urinary deoxypyridinoline excretion and enhanced alkaline phosphatase activity.